Effects of abdominal sepsis in the healing of abdominal wall: experimental study in rats - Brandão,Alexandre Malta (2011)
PURPOSE: To evaluate the influence of sepsis in the process of wound healing in the abdominal wall. METHODS: 40 rats divided into two groups of twenty animals: group of study (E) - septic, and the control group (C) - not septic. The two groups were divided into subgroups of 10 to be killed on the third day (n = 10) or seventh (n = 10) postoperative. Sepsis was induced by ligation and puncture of the cecum. We performed also the section and anastomosis in left colon. The synthesis of the abdominal wall was made with 3-0 silk thread. On the day of re-laparotomy, the abdominal wall was removed for analysis of the breaking strength and histopathological analysis. RESULTS: The mean breaking strength was at third day: E group (1.44 ± 1.22) and C group (0.35 ± 0.46). At seventh day the mean breaking strength was: E group (13.01 ± 7.09) and C group (11.66 ± 7.38). There was statistical difference in tensile strength. E group at third day with control group (p = 0.019). CONCLUSION: The induction of peritoneal sepsis reduced the breaking strength of the abdominal wall on the third day after surgery.